2018
DOI: 10.3390/nu11010066
|View full text |Cite
|
Sign up to set email alerts
|

A High Adherence to Six Food Targets of the Mediterranean Diet in the Late First Trimester is Associated with a Reduction in the Risk of Materno-Foetal Outcomes: The St. Carlos Gestational Diabetes Mellitus Prevention Study

Abstract: A prenatal diet affects materno-foetal outcomes. This is a post hoc analysis of the St. Carlos gestational diabetes mellitus (GDM) Prevention Study. It aims to evaluate the effect of a late first-trimester (>12 gestational weeks) degree of adherence to a MedDiet pattern—based on six food targets—on a composite of materno-foetal outcomes (CMFCs). The CMFCs were defined as having emergency C-section, perineal trauma, pregnancy-induced hypertension and preeclampsia, prematurity, large-for-gestational-age, and/or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
60
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(70 citation statements)
references
References 31 publications
3
60
0
7
Order By: Relevance
“…Although we support the role of most these proteins in the pathogenesis of diabetes mellitus and their possible impact on fetus growth and development, we incline to consider these proteins as the secondary response effectors with low (or insufficient) specificity and selectivity. In this way, we limited only a small fraction of proteins that met the criteria of (1) sufficient frequency, (2) rare mentioning in regard of other pathologies, (3) relation to the disturbed insulin metabolism and accompanied immune reaction and (4) possibility to connect proteins of interest into proposed molecular mechanism reflecting the process of insulin resistance and associated diabetic fetopathy. At the same time, it was demonstrated that GDM groups (G01 and G02, Supplementary Appendix C and Supplementary Appendix D) are featured by the largest number of specifically altered proteins: there were 56 proteins attributed for G01 (healthy newborns) whereas 37 proteins were specifically revealed for G02 (newborns with signs of DF).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although we support the role of most these proteins in the pathogenesis of diabetes mellitus and their possible impact on fetus growth and development, we incline to consider these proteins as the secondary response effectors with low (or insufficient) specificity and selectivity. In this way, we limited only a small fraction of proteins that met the criteria of (1) sufficient frequency, (2) rare mentioning in regard of other pathologies, (3) relation to the disturbed insulin metabolism and accompanied immune reaction and (4) possibility to connect proteins of interest into proposed molecular mechanism reflecting the process of insulin resistance and associated diabetic fetopathy. At the same time, it was demonstrated that GDM groups (G01 and G02, Supplementary Appendix C and Supplementary Appendix D) are featured by the largest number of specifically altered proteins: there were 56 proteins attributed for G01 (healthy newborns) whereas 37 proteins were specifically revealed for G02 (newborns with signs of DF).…”
Section: Resultsmentioning
confidence: 99%
“…Conclusion: The combination of the measured markers may assist (AUC = 0.893 (CI 95%, 0.785-0.980) in establishing the clinical finding of the developing DF especially in patients with GDM who are at the highest risk of chronic insulin resistance.Cells 2020, 9, 1032 2 of 22 mellitus, type 2 diabetes mellitus (T2DM) or gestational diabetes mellitus (GDM) suffered by pregnant women. Diabetic fetopathy is the cause of premature birth, chronic hypoxia, respiratory depression, asphyxia of the fetus at birth, accompanied by various metabolic disorders, and can also be the cause of newborns death [1][2][3]. This is one of the most common forms of obstetric complications and perinatal losses evoked from hyperglycemia manifested in a disturbance of glucose tolerance and occurred or was first recognized during pregnancy [4].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Those who consumed ≥3 servings/day of dairy products at 24-28 gestational weeks (GWs) were included and analyzed (n=2004). The population was stratified into three groups according to intake of fat-free dairy productsskimmed milk and fat-free yoghurt and cheese-(days/ week): infrequent (1-2), average (3)(4)(5)(6) and regular (7). Logistic regression analysis compared ORs (95% CI) for GDM and CMFO between the three groups (where the group of reference was the 'infrequent' intake group).…”
Section: Introductionmentioning
confidence: 99%